The Achievement of Middle School Students’ Mathematical Problem Solving Abilities through Project-Based Learning Models - Fisher, Dahlia; Kusumah, Yaya Sukjaya; Dahlan, Jarnawi Afgani (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
This research aims to determine the use of project-based learning (PjBL) in the achievement of students' mathematical problem-solving abilities. The variables in this research were PjBL and mathematical problem-solving abilities. The instrument in this research was a description test of mathematical problem-solving abilities, which was analyzed by testing the hypothesis using the Mann Whitney U test. The results showed that the average value of students learning using PjBL was higher than students learning using conventional models. The results of the Mann Whitney test show that learning using PjBL is effective in improving students' mathematical problem-solving abilities.